The influence of lubricant slurries on skin friction resistance in pipe jacking - Reilly, Ciaran C. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
The use of bentonite and polymer slurries as lubricants to reduce jacking force has long been established practice in pipe jacking and microtunnelling, with reductions in the skin frictional resistance component of jacking force of up to 90% being reported. The objective of this research is to improve the understanding of the mechanisms of action of these pipe- jacking lubricants. Field case histories are presented where the influence of lubricants is shown. Laboratory studies are described where the effects of pressurised and unpressurised lubricant slurries in the interface between concrete jacking pipes and coarse¬grained and fine-grained soils are quantified.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin